A linguagem de Ariano Suassuna: um glossário léxico-semântico - Oliveira, Uélida Dantas de (2018)
In the present study, we have as general objective to elaborate a lexical-semantic glossary of the lexical choices of the writer Ariano Suassuna, analyzing his lexicon in the works O casamento suspeitoso (2012), Farsa da boa preguiça (2014) and O santo e a porca (2011). With this purpose, we selected lexias in the corpus for the elaboration of the glossary, highlighting the relevance of lexias of regional Northeastern nature, analyzing the regional lexicon aspect. Another important objective for the elaboration of the glossary is the question of lexias configuring archaisms or neologisms. For the development of the study, in the beginning, we performed bibliographical research on lexicography and the critical fortune on Ariano Suassuna, as well as the readings of the author's books. The bibliography consulted about the author was Victor e Lins (2007) and Tavares (2007). For the theoretical basis, according to the linguistic theories of Lexicon and its sciences, lexicology and lexicography, we use the theory of Barbosa (1981), Biderman (2001), Vilela (1995) and Ilari (2012) as well as the theories "lexical neologism" and "linguistic archaism", with the help of Carvalho (1984), also explaining questions about dictionaries, with the help of Borba (2003), among others. For the preparation of the glossary, lexicographic sheets were filled out, with the entries selected in the analysis of the corpus, and then whether or not they were worded. This activity was carried out with the help of the Portuguese language dictionaries of Ferreira (2010) and Houaiss (2012), among others, and of the Northeastern regional dictionaries of Navarro (1998) and Cabral (1982), among others.